2019
DOI: 10.1080/01605682.2018.1487815
|View full text |Cite
|
Sign up to set email alerts
|

A pricing model for Internet of Things-based fleet services to support equipment sales

Abstract: Servitization and rapid technological development have made data-based services a feasible way for many manufacturing companies to increase their cash flow and support their core products. In this paper, an analytical model is presented for studying the development costs and pricing of new Internet of Things -based services for especially populations, or fleets, of industrial production equipment and machines. The model suggests the optimal price of a fleet service as a function of the life cycle of the servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…, 2020). Finally, a few articles use other approaches, such as modeling (Marttonen-Arola et al. , 2019), simulation (Ruutu et al.…”
Section: Structuring Dsi-related Research: Ontology Theory Context An...mentioning
confidence: 99%
See 2 more Smart Citations
“…, 2020). Finally, a few articles use other approaches, such as modeling (Marttonen-Arola et al. , 2019), simulation (Ruutu et al.…”
Section: Structuring Dsi-related Research: Ontology Theory Context An...mentioning
confidence: 99%
“…, 2020). Few other studies focus on manufacturing, and they are found at the intersection of the service innovation and digital servitization clusters, mixing concepts and references from both research streams (Chester Goduscheit and Faullant, 2018; Marttonen-Arola et al. , 2019; Opazo-Basáez et al.…”
Section: Structuring Dsi-related Research: Ontology Theory Context An...mentioning
confidence: 99%
See 1 more Smart Citation